Roman Law in streaming - Vieira Malanovicz, Aline (Romanitas - Revista de Estudos Grecolatinos, 2020)
In the last few decades, there has been an increase in the interest aroused by Classical Studies. At the same time, technologies have evolved, as have teaching methods. One of the themes present in research projects on the past of Rome is Roman Law. And, currently, for their teaching, active methodologies using technology are researched. This research aims to present a work proposal for the teaching-learning of Roman Law based on active methodology using scenes from films and television series. A filmographic survey is carried out focused on the theme of Roman Law, carried out in movie and series streaming channels. Some possible analyzes are then exemplified on the approach of certain institutes of Roman Law in selected films. The didactic activity plan with practices of searching for films and scenes, reflection on the institutes and relational analysis and interpretation is proposed. We conclude that there is ample potential for contributing, to Classical Studies, from the use of films and series for reflection on the society of ancient Rome and Roman Law.